Katiang palaung of Hsipaw: Phonology and classification - Supakit Buakaw (2018)
© Universitat de Barcelona Palaung, which belongs to Palaungic branch of Mon-Khmer, is a diverse language. There are numerous dialects or varieties spoken in the area of northern Shan State of Myanmar. The well-known Palaung dialects in this area are those of Ta-ang dialect of Namhsan and Rumai of Namhkam. Another location in northern Shan State where Palaung villages are found is Hsipaw. This paper aims to explore the phonological system of Katiang, a variety of Palaung spoken in Man Lwae village of Hsipaw in northern Shan State, Myanmar. Also, Katiang sound system will be compared with those dialects of Yunnan, China, Kengtung in Myanmar and Chiang Mai in Thailand. This paper proposes that the Katiang is a link between the Palaung group of dialects spoken in Dehong, Yunnan and the group of southern Palaung dialects spoken in southern Shan State, Myanmar and Chiang Mai, Thailand.